1998
DOI: 10.1016/s0926-9959(98)00014-2
|View full text |Cite
|
Sign up to set email alerts
|

Generalized cutaneous leishmaniasis in acquired immunodeficiency syndrome

Abstract: The immunosuppression due to HIV/AIDS seen in this patient may explain the dissemination of the lesions, but the positive specific response to leishmanial antigen may explain the good response to the antimonial treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The worsening of clinical manifestations, multiple lesions and high degree of relapses post-treatment in ATL patients co-infected with HIV were previously described ( Rosatelli et al, 1998 ; Puig and Pradinaud, 2003 ; Lindoso et al, 2009 , 2016 ; Giavedoni et al, 2015 ; Calvopina et al, 2017 ). In a study of fifteen cases of AIDS/TL, Lindoso et al (2009) observed mucosal lesions progress in 80% of the patients, disseminated lesions in 60% and genital lesions in 27% of the patients.…”
Section: The Host Point Of Viewmentioning
confidence: 72%
“…The worsening of clinical manifestations, multiple lesions and high degree of relapses post-treatment in ATL patients co-infected with HIV were previously described ( Rosatelli et al, 1998 ; Puig and Pradinaud, 2003 ; Lindoso et al, 2009 , 2016 ; Giavedoni et al, 2015 ; Calvopina et al, 2017 ). In a study of fifteen cases of AIDS/TL, Lindoso et al (2009) observed mucosal lesions progress in 80% of the patients, disseminated lesions in 60% and genital lesions in 27% of the patients.…”
Section: The Host Point Of Viewmentioning
confidence: 72%
“…[6][7][8][9][10][11][12][13] However, reports on clinical manifestations of tegumentary leishmaniasis in HIV-infected patients are scarce. The lesions described so far range from isolated papules, plaques or ulcers on exposed areas similar to those found in nonimmunosuppressed patients or in nonHIVinfected patients 7,14,15 to disseminated ulcers or plaques.…”
Section: Discussionmentioning
confidence: 99%
“…Poor response to therapy could be secondary to severe immunodepression and suboptimal therapy. Currently, the standardized treatment of CL for immunocompetent patients is either intralesional or systemic antimonials, and HIV-infected patients have also shown a good response to antimonials [ 13 ]. Liposomal amphotericine B has also been found to be effective [ 14 ].…”
Section: Discussionmentioning
confidence: 99%